Apuntes sobre tres taxones de la provincia de Lugo (Galicia, NO España) - de la Peña Lastra, Saúl; González-Martínez, Xosé Ignacio; Rodríguez-Guitián, Manuel Antonio (Servizo de Publicacións e Intercambio Científico, Universidade de Santiago de Compostela, 2016)
Se presentan tres taxones de flora vascular gallega recolectados en la provincia de Lugo, entre los que se encuentran 2 novedades regionales [Ophioglossum azoricum K. Presl, Viola suavis M. Bieb. subsp. catalonica (W. Becker) O. Bolòs & Vigo]. Además, se incluye una revisión sobre la distribución del pteridófito Botrychium lunaria (L.) Sw. en territorio gallego. Los pliegos testigo se hallan depositados en los Herbarios LUGO y SANT de la Univesidade de Santiago de Compostela. In this note, information on three taxa of galician vascular flora is presented, all of them collected in the province of Lugo. Two of them were collected for the first time in Galicia [Ophioglossum azoricum K. Presl, Viola suavis M. Bieb. subsp. catalonica (W. Becker) O. Bolòs & Vigo)]. In addition, a revision about the distribution of Botrychium lunaria (L.) Sw. in Galicia is also included. All the cited specimens are deposited at the LUGO and SANT Herbaria.